Cultural Constructions of Demographic Inquiry: Experiences of an Expatriate Researcher in Tunisia - Beaujot, Roderic (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1985)
The average number of children per woman in Tunisia has declined from about seven in the mid 1960’s to about five in the early 1980’s, but the change has been slower over the last part of this period. In attempting to understand Tunisian society and its childbearing situation, we address questions of (1) sex roles, (2) conflicts over models of development and (3) tribal loyalties. The state has attempted to change sex roles, but there remain powerful traditional forces, especially from men, giving priority to women’s family roles. The conflict between Western and Islamic models of development implies that there is a wide element of ambivalence as people try to seek the advantages of both the small (Western) family and the large family corresponding to cultural traditions. For many, four children represent a type of compromise: “not too many, not too few”. Given the ways in which tribal loyalties become part of institutional dynamics, certain groups have come to perceive that Family Planning is acting not for them but for its own benefit. In the course of reconstructing these fertility dynamics, the author also stresses the experiences through which he learnt to situate the relevant issues.